Essentials of Asian cuisine : fundamentals and favorite recipes - Trang, Corinne (New York : Simon & Schuster, 2003)
Provides instructions and recipes for creating foods including Korean spicy grilled pork, Japanese roasted eggplant with sweet miso sauce, Philippine garlic fried rice, Vietnamese spring rolls, and red bean ice cream.
Essential ingredients : the asian pantry -- Equipment and techniques : the basics -- Fundamentals : an overview -- Condiments -- Stocks, palate cleansers, and starter soups -- Rice, noodles, dumplings, and breads -- Vegetables and herbs -- Fish and seafood -- Meat and poultry -- Sweets and drinks -- Food rituals and sample menus.
Includes bibliographical references (p. 567-568) and index.
Keywords: Cooking, Asian